Pelatihan Perwasitan Sepakbola pada Guru Olahraga Sekolah Dasar Batang Kulim Kecamatan Pangkalan Kuras Kabupaten Pelalawan - Prima Aspa, Agus Prima Aspa; Kristiagust, Kristiagust; Rusmanto , Rusmanto; Mandan, Ali; Hendro, Yogi; Prayogo Ramadhan , Danang (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
One of the oldest football problems, particularly in Indonesia, is the referee dilemma. Even though referees play a crucial role in the quality of a game, news regarding the plight of Indonesian football referees—from security assurances during games to salary delays—frequently receives less attention. Even yet, the caliber of the referee who serves as the match's leader has a significant impact on the match's overall quality. It is understandable that the referee will ultimately fail to provide exceptional leadership if the welfare and safety of the match equipment are disregarded. This may be inextricably linked to the development of a culture in which referees are the primary occupation and profession in Indonesia. Referees are the primary employees in Indonesia, therefore it makes perfect sense for them to rely on the money they get from each game they officiate. Through age group tournaments and internal contests, ASKAB Pelalawan Regency regularly coaches football. The Pengcab's contests require the assistance of a knowledgeable, unbiased, and competent referee in making decisions. By doing this, the elements of a game are not at a disadvantage, and the competition may proceed in a fun way and be held on a regular basis.